Application of deep learning algorithms in lung sound classification: A systematic review since 2015 - Sundaraj, Kenneth; Neili, Zakaria (Seventh Sense Research Group, 2025)
The article systematically explored the application of deep learning for lung sound classification in three popular scientific databases – PubMed, ScienceDirect and IEEE Xplore, for articles published between 2015 and 2024. Using specific keywords combined with deep learning terms, we identified 1428 articles. Based on their titles, abstracts and content, 33 articles were deemed relevant and selected for review. The article’s thorough analysis revealed that deep learning algorithms have outperformed traditional machine learning techniques in lung sound classification.